Machinery's handbook - Oberg, Erik, 1881-1951; Jones, Franklin D., 1879-1967; Horton, Holbrook Lynedon, 1907-; Ryffel, Henry H. (Industrial Press, Incorporated, 2016)
For more than 100 years, Machinery's Handbook has been the most popular reference work in metalworking, design, engineering and manufacturing facilities, and technical schools and colleges throughout the world. It is universally acknowledged as an extraordinarily authoritative, comprehensive, and practical tool, providing its users with the most fundamental and essential aspects of sophisticated manufacturing practice. The 30th edition of the "Bible of the Metalworking Industries" contains major revisions of existing content, as well as new material on a variety of topics. It is the essential reference for mechanical, manufacturing, and industrial engineers, designers, draftsmen, toolmakers, machinists, engineering and technology students, and the serious home hobbyist.--AMAZON.